2009
DOI: 10.1158/1078-0432.ccr-08-2944
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Ritonavir Strongly Enhances the Apparent Oral Bioavailability of Docetaxel in Patients with Solid Tumors

Abstract: Purpose: To enhance the systemic exposure to oral docetaxel by coadministration of ritonavir, an efficacious inhibitor of CYP 3A4 with minor P-glycoprotein inhibiting effects, in patients with cancer. Experimental Design: A proof-of-concept study was carried out in 12 patients with solid tumors. The first cohort of patients (n = 4) received 10 mg and the subsequent cohort (n = 8) 100 mg of oral docetaxel, coadministered with 100 mg oral ritonavir randomized simultaneously or ritonavir given 60 minutes before d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…The heat map of Bliss scores for IGROV-1 (Fig. 1C) shows that there are greater than additive effects across a clinically relevant range of doses for both compounds (11,17). In contrast, the TOV21G cell line exhibited minimal synergy across a small dose range.…”
Section: Resultsmentioning
confidence: 97%
“…The heat map of Bliss scores for IGROV-1 (Fig. 1C) shows that there are greater than additive effects across a clinically relevant range of doses for both compounds (11,17). In contrast, the TOV21G cell line exhibited minimal synergy across a small dose range.…”
Section: Resultsmentioning
confidence: 97%
“…After 24 hours, cells were treated with navitoclax (dose range ¼ 0.12-3.3 mmol/L) and paclitaxel or DTX (dose range ¼ 3-100 nmol/L) in a 5 Â 5 matrix of concentrations chosen to encompass clinically relevant doses (23,24). Each treatment was done in quadruplicate.…”
Section: Cell Viability Assay and Western Blottingmentioning
confidence: 99%
“…14,15 Several studies have shown that the oral bioavailability of docetaxel can be enhanced significantly by coadministration of Pgp and/or CYP3A inhibitors, such as cyclosporin A, ritonavir, interferon-alpha, and ontogen (ONT-093). 14,[16][17][18] However, the usefulness of these drugs in clinical practice is limited, especially for repeated administration, because of the risk of side effects, which include immunosuppression. 19 Solid lipid nanoparticles (SLNs) are submicron (50-1,000 nm) colloidal particulate systems composed of physiologically tolerable lipid components, which remain in the solid state at room temperature.…”
Section: Introductionmentioning
confidence: 99%